MOOI INDIE - Rini Riris Setyowati; Aman Aman (Jantra., 2019)
The Mooi Indie has been considered as a painting style that was developing in Nusantara during the Colonial Government of Dutch Indies. The depiction of Nusantara’s beautiful scenery has become a implanted characteristic of the Mooi Indie painting until today. Mooi Indie was considered as the starting point of the development of modern painting. This literature study has revealed the following information. The artists through their works received appreciation because they had presented the natural beauty of the Dutch East Indies to the world. Appearing in the midst of the elite of Dutch colonial and the indigenous noblemen, Mooi Indie became the representation of grandeur, wealth, and the beauty of Nusantara. The objects of paint of Mooi Indie artists were farmer community and the beautiful natural sceneries of Dutch East Indies. In addition, practicing this genre they could also see the misery and concern of the community being portrayed. The results of this study show that Mooi Indie paintings were able to place beautiful mountains, rice fields, plants, and society into one frame. Another implied message is this painting genre was able to place the people’s agrarian culture in the proper composition. It is not surprising that Mooi Indie’s painting has become part of history as well as an evidence of the existence of an agrarian culture in Nusantara.